Usulan Strategi Pemasaran Universitas Al Azhar Indonesia Menggunakan Metode K-Means Clustering - Arsyad, Aisyah Tiar; Nurlatifah, Hanny; Sunarmo, Sunarmo (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
In 2022, the University Al Azhar Indonesia (UAI) was in the second phase of expansion, focusing on increasing the influx of new students. Each year, UAI allocated funds to execute diverse promotional strategies. However, the effectiveness of the undertaken promotional measures is deemed suboptimal, as the student admissions continue to exhibit fluctuations. To address this issue, researchers have employed the data mining method utilizing the K-Means Clustering algorithm. This study adopts both qualitative and quantitative approaches. Following the data cleaning stage, the initial sample size of 4,342 students is reduced to 2,650. The K-Means Clustering analysis identifies three clusters: the main cluster, minimum cluster, and adaptive cluster. Based on the characteristic data within the first cluster, it is recommended that UAI prioritizes promotional efforts towards students from private high schools in the Jabodetabek area. Additionally, the marketing communication mix, including brochures, banners, printed media, television, and radio, needs to be reassessed. In executing promotional strategies, UAI is advised to carefully consider the unique characteristics of each cluster and to maximize the utilization of social media and websites by incorporating elements of the 7C Framework.Keywords - K-Means, Clustering, Promotion Strategy